PENGARUH PENANAMAN MODAL ASING, CADANGAN DEVISA, DAN APBN TERHADAP UTANG LUAR NEGERI INDONESIA MELALUI IMPOR TAHUN 1996-2015 - Kusuma Dewi Putu; Urmila Dewi Made Heny (PIRAMIDA, 2019)
International trade is a cross-border trade relationship between the exchange of goods or services in export and import activities. Foreign debt is an alternative made by a country especially in the form of loans due to various reasons that are rational. The purpose of this study is to determine the direct and indirect effects of foreign investment, foreign exchange reserves, state revenues, state expenditures, imports, and foreign debt. This study uses secondary data from period 1996-2015 with path analysis technique (path analysis). From this research, it is found that foreign investment has no significant negative effect on imports, revenues and expenditures of the state has no significant negative effect on foreign debt. Foreign investment, foreign exchange reserves, state revenues, and state expenditures have no direct effect on foreign debt through imports in Indonesia. Imports have no direct effect on external debt because foreign debt is neutral and has no effect on international trade (import). Imports are not an intervening variable on foreign debt because imports depend on state revenues rather than revenues earned from abroad.